The Influence of Work Discipline, Competency, and Motivation to Employee Performance on PT. SPV - Joko Rustanto; Fajar Adhi Purwaningrum (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Employee performance data of PT. The SPV in 2024 shows that the average employee performance is still not optimal. Several causative factors are suspected to be due to low work discipline, competence and motivation of employees. This study aims to obtain empirical evidence and obtain clarity of phenomena and conclusions about the influence of work discipline, competence, and motivation on the performance of employees of PT. SPV both partially and simultaneously. For research purposes, the methods used in this study consist of descriptive and verifiable methods. Data collection was carried out by means of field research, through the distribution of questionnaires that were structured using the Likert scale. Data analysis to describe each variable using scale range analysis. Meanwhile, to describe the influence of work discipline, competence and motivation on employee performance using path analysis. The results of the study showed: 1) Work discipline is in the high-scale range, competence is on a high scale, motivation is in the high-scale range and employee performance is in the high-scale range, 2) Work discipline, competence and motivation partially affect the performance of PT. SPV, and 3) Work discipline, competence and motivation simultaneously affect the performance of employees of PT. SPV with an amount of 31.0%.